Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
-7(1 + 7n) = 36 - 6n
-7(1) - 7(7n) = 36 - 6n
-7 - 49n = 36 - 6n
+49n +49n
-7 = 36 + 43n
-36 -36
-43 = 43n
43 43
-1 = n
-7(1) - 7(7n) = 36 - 6n
-7 - 49n = 36 - 6n
+49n +49n
-7 = 36 + 43n
-36 -36
-43 = 43n
43 43
-1 = n
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.